Formation of student personality’s physical culture as subject of professional functioning - O.V. Otravenko (Physical Education of Students, 2015)
Purpose: generalization of experience of higher educational establishments’ future specialists’ professional training, oriented on formation of students’ personalities’ physical culture. Material: we questioned students (n=50) and institute teachers (n=30). Results: it was found that for increase of future specialists’ professional fitness effectiveness it was important to consider orientation of educational process on formation of student personality’s physical culture. Besides, it was noticed that professional fitness of future specialists is greatly influenced by implementation of modern technologies of formation of students’ physical culture in educational-learning process. Physical education means, oriented on aesthetic are of great health related and recreation significance. Conclusions: educational process shall be oriented on support of active motor functioning, motivation for physical exercises’ and healthy life style practicing.